2014
DOI: 10.1186/bf03352140
|View full text |Cite
|
Sign up to set email alerts
|

Brightness of the solar F-corona

Abstract: We discuss our present knowledge about the brightness of the solar F-corona in the wavelength range from the visible to the middle infrared. From the general trend of the observational data, the F-corona is regarded as the continuous extension of the zodiacal light at smaller elongation of the line of sight. A contribution of thermal emission from dust is indicated by the increasing F-coronal brightness in comparison to the solar spectrum towards longer wavelength. As compared with the F-coronal brightness, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 50 publications
4
42
0
Order By: Relevance
“…In recent years, several authors have investigated the intensity of the F corona. For instance, Kimura & Mann (1998) discussed the emission of the interplanetary dust in the wavelength range from the visible to the mid-infrared and showed that the hump of the near-infrared brightness at 4 R , sometimes observed in corona, is related to the physical properties of dust grains along the LOS rather than to the existence of a spherical dust ring. The hypothesis of an axisymmetric model of the F corona from the analysis of its morphology and photometry was first proposed by Koutchmy & Lamy (1985); they studied the infrared observations of the dust grains and obtained an expression of the F-corona intensity as a function of the heliocentric distance, which is the most quoted at present.…”
Section: F-corona Modellingmentioning
confidence: 99%
“…In recent years, several authors have investigated the intensity of the F corona. For instance, Kimura & Mann (1998) discussed the emission of the interplanetary dust in the wavelength range from the visible to the mid-infrared and showed that the hump of the near-infrared brightness at 4 R , sometimes observed in corona, is related to the physical properties of dust grains along the LOS rather than to the existence of a spherical dust ring. The hypothesis of an axisymmetric model of the F corona from the analysis of its morphology and photometry was first proposed by Koutchmy & Lamy (1985); they studied the infrared observations of the dust grains and obtained an expression of the F-corona intensity as a function of the heliocentric distance, which is the most quoted at present.…”
Section: F-corona Modellingmentioning
confidence: 99%
“…It might be worthwhile to recognize that near-infrared excess emission observed in the solar F-corona is a similar enigmatic phenomenon. The excess emission of the solar F-corona has been detected around 4 R from the Sun until 1983 in the H and J bands and until 1973 in the K and L bands, but its origin is still an open question (Kimura and Mann, 1998). Here we cannot help but wonder whether the hot dust populations could be replenished by the super-catastrophic disruption of sub-kilometer to kilometer sized planetesimals in the vicinity of the star (cf.…”
Section: Debris Disksmentioning
confidence: 99%
“…It is thought that the F-corona emission is weakly polarized or unpolarized, while the electron-scattered K corona is known to be strongly polarized with the electric field vector oscillating in a plane parallel to the limb tangent (e.g., Billings 1966;Kimura & Mann 1998). Blackwell & Petford (1966a, 1966b used spectroscopic separation of the F and K components to show that the F corona is about 0.2% polarized at 10 R and 0.5% polarized at 15 R .…”
Section: Introductionmentioning
confidence: 99%
“…The F corona models have significant uncertainty, and the importance of this uncertainty increases at larger heights above the limb where the F corona increasingly dominates the unpolarized signal. The current state of knowledge of the F corona and its optical/IR properties, including polarization, is reviewed in Kimura & Mann (1998). There is more discussion of dust physics in Blackwell et al (1967a) and Mann et al (2004).…”
Section: Introductionmentioning
confidence: 99%